Retratos em (re)vista : do estúdio à imprensa ilustrada em Bagé, 1890-1921 - Brasil, Luísa Kuhl (2013)
This study discusses the construction of social roles through the artistic works produced by the photographer José Greco in early twentieth century Brazil, in the city of Bagé. Using the concepts of visual culture and material culture, this paper analyzes the portraits and studio portraits published in Phenix Magazine, in 1921. Based on the notion that photography was an instrument of visual intermediation between the public and private spheres, this study analyzes those images focusing on its socializing nature.